IMPLEMENTASI QANUN NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT DI KOTA BANDA ACEH PROVINSI ACEH - Selvia Junita Praja; Wia Ulfa (Fakultas Politik Pemerintahan IPDN, 2020)
Qanun Jinayat is a legal product established with the aim of reducing the number of violations of Islamic law in the city of Banda Aceh. But the facts show that the implementation of this qanun over the past five years has not reduced violations of Islamic law. This is interesting to do research considering the presence of the qanun as the norm that enforces Islamic Sharia has not been able to reduce the level of violation. For this reason, this research would like to describe the implementation of the Qanun Jinayat and the factors that cause the qanun become ineffective. This research uses qualitative method with descriptive approach. The Research data collected were using interview and documentation study technique. Research findings reveal that the process of implementing Qanun No. 6 of 2014 concerning Jinayat Law has not gone well. Factors that cause the ineffectiveness of the implementation of the Qanun Jinayat in Banda Aceh City are human resources that lack adequate quality, management of financial resources that are not optimal and the availability of facilities and infrastructure that have not been good. Keywords : Implementation, Qanun Jinayat